2019
DOI: 10.3390/ijms20102477
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Preconditioning Enhances Therapeutic Efficacy of Human Wharton’s Jelly–Derived Mesenchymal Stem Cells in Severe Neonatal Hypoxic Ischemic Encephalopathy

Abstract: We investigated whether thrombin preconditioning of human Wharton’s jelly–derived mesenchymal stem cells (MSCs) improves paracrine potency and thus the therapeutic efficacy of naïve MSCs against severe hypoxic ischemic encephalopathy (HIE). Thrombin preconditioning significantly enhances the neuroprotective anti-oxidative, anti-apoptotic, and anti-cytotoxic effects of naïve MSCs against oxygen–glucose deprivation (OGD) of cortical neurons in vitro. Severe HIE was induced in vivo using unilateral carotid artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…In this study, the MWM spatial probe test indicated that SHED transplantation partially reversed cognitive impairment in rats after the induction of CCI. Previous studies have reported that bone marrow mesenchymal stem cells (BMMSCs) can play a neuroprotective role and improve the learning and memory ability of CCI rats [9]. However, SHED show a stronger proliferation than BMMSCs and have a multidirectional differentiation potential, in particular, a strong neuronal differentiation ability, as well as significant immunomodulatory effects [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the MWM spatial probe test indicated that SHED transplantation partially reversed cognitive impairment in rats after the induction of CCI. Previous studies have reported that bone marrow mesenchymal stem cells (BMMSCs) can play a neuroprotective role and improve the learning and memory ability of CCI rats [9]. However, SHED show a stronger proliferation than BMMSCs and have a multidirectional differentiation potential, in particular, a strong neuronal differentiation ability, as well as significant immunomodulatory effects [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic MSC transplantation (MSCT) has been successfully used to treat a variety of human diseases, such as systemic lupus erythematosus, myocardial infarction, and inflammatory bowel disease [6,7]. Recently, studies have reported that MSCT promoted neurorecovery and ameliorated ischemic brain injuries [8,9]. MSCT restored memory through promoting endogenous neurogenesis and synaptic remodeling in AD mice and improved early cognitive functions and daily living activities in VaD patients [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the angiogenic role of PBMCs was evaluated, because they contain MPCs with significant angiogenic effects and due to the potential applications within tissue engineering and regenerative medicine. Likewise, we explored the role of thrombin because several studies had suggested that thrombin preconditioning enhances therapeutic efficacy of transplanted progenitor cells, probably through modulation of secretion of growth factors and cytokines like VEGF and HGF (Kim et al, ; Mühleder et al, ; Tarzami, Wang, Li, Green, & Singh, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have examined the effects of thrombin. Exosomes from MSCs pre-conditioned with thrombin (thrombin-primed MSCs) improved proliferation, migration, and tube formation by HUVECs in vitro and cutaneous wound healing in vivo [124]. In another study, exosomes from thrombin-primed MSCs from Wharton's Jelly showed enhanced anti-inflammatory and anti-apoptotic effects, resulting in attenuation of brain infarction in a rat model of hypoxic ischemic encephalopathy [124].…”
Section: Pre-conditioning Of Mscs With Biomolecules or Chemicalsmentioning
confidence: 99%
“…Exosomes from MSCs pre-conditioned with thrombin (thrombin-primed MSCs) improved proliferation, migration, and tube formation by HUVECs in vitro and cutaneous wound healing in vivo [124]. In another study, exosomes from thrombin-primed MSCs from Wharton's Jelly showed enhanced anti-inflammatory and anti-apoptotic effects, resulting in attenuation of brain infarction in a rat model of hypoxic ischemic encephalopathy [124]. Exosomes from MSCs pre-conditioned with melatonin decreased the expression of HIF1α, ICAM1, IL1B and NFkB, and increased the expression of BCL2, HO1, IL10 and VEGF in a rat model of renal ischemia-reperfusion injury [125], whereas exosomes from MSCs pre-conditioned with advanced glycation end products contained a high level of miR-146a and inhibited calcification of vascular smooth muscle cells in vitro [126].…”
Section: Pre-conditioning Of Mscs With Biomolecules or Chemicalsmentioning
confidence: 99%